Masters in Collective Health: pathway of challenges and possibilities - López López, María Victoria; Arias López, Beatriz Elena; Gaviria Noreña, Dora Lucía (Investigación y Educación en Enfermería, 2015)
The masters program in Collective Health at Universidad de Antioquia reaches its 20 years. This fact constitutes a motive of satisfaction, recognition, and gratitude: to the directors at Universidad de Antioquia who have made it possible for this program to be maintained and have the parameters of a graduate program, sustainability, and evaluation established in the institution and in the national and international context; to the students and alumni who have opened the field of questions and have positioned relevant problems and new debates; and to the professors who in the most committed manner have contributed with their experiences, reflections, and knowledge acquired through research, formation, and outreach and with the best of their intellectual work. How to cite this article: López MV, Arias BE, Gaviria DL. Masters in Collective Health: pathway of challenges and possibilities. Invest Educ Enferm. 2015; 33(2): 191-193.